Expected budget deficits and interest rate swap spreads - Evidence for France, Germany and Italy - Kirsten H. Heppke-Falk; Felix P. Hüfner (Deutsche Bundesbank, 2004)
This study analyses whether expected budget deficits have an impact on interest rate swap spreads in France, Germany and Italy. We use monthly deficit forecasts from financial market participants to take the forward-looking behaviour of financial markets into account. Results of a SUR estimation show no significant impact of expected deficits on swap spreads over the whole sample period (1994-2004). However, we find an increase in market discipline for Germany and France since the signing of the Stability and Growth Pact, and for Germany also since the start of European monetary union.
Keywords: E43; H62; E62; C33; 330; Budget deficits; interest rate swap spreads; EMU; Stability and Growth Pact; Haushaltsdefizit; Zinsswap; Deutschland; Frankreich; Italien